2002
DOI: 10.1103/physrevb.66.195108
|View full text |Cite
|
Sign up to set email alerts
|

Tunable photonic band gap in self-assembled clusters of floating magnetic particles

Abstract: We fabricated a 3D photonic crystal consisting of metal coated disk-shaped magnetic particles floating at the liquid-air interface inside a stack of containers. The particles self-assemble into an ordered crystal whose in-plane lattice constant can be varied by external magnetic field in very broad limits. This crystal exhibits photonic stopband at microwave frequencies. The stopband can be continuously tuned by external magnetic field until complete disappearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…One of them, band-tuning via field dependence of the permeability was discussed in a recent review [74]. A quite different magnetic mechanism has been demonstrated by Saado and co-workers [75] in a 3D photonic crystal composed of metal coated disk-shaped magnetic particles floating at a liquid-air interface. They showed that the lattice constant of an ordered array of these magnetic particles can be controlled by an external magnetic field.…”
Section: Tunable Photonic Crystalsmentioning
confidence: 97%
“…One of them, band-tuning via field dependence of the permeability was discussed in a recent review [74]. A quite different magnetic mechanism has been demonstrated by Saado and co-workers [75] in a 3D photonic crystal composed of metal coated disk-shaped magnetic particles floating at a liquid-air interface. They showed that the lattice constant of an ordered array of these magnetic particles can be controlled by an external magnetic field.…”
Section: Tunable Photonic Crystalsmentioning
confidence: 97%
“…Review articles about the theory and the experimental realizations of MPCs were published by Lyubchanskii et al (2003), Zvezdin and Belotelov (2004), and Inoue (2006). Incorporation of magnetic components into PCs can lead to new and interesting phenomena of magneto-optics such as enhanced MCB and MLB (Inoue and Fujii, 1997;Steel, Levy and Osgood, 2000;Levy, Yang and Steel, 2001;Saado, Golosovsky, Davidov and Frenkel, 2002;Dolgova et al, 2004). The first PC structures were one-dimensional multilayers with dielectric mirrors (λ/4 stacks of materials with high and low refractive index) and a transparent magnetic λ/2 Fabry-Pérot cavity ( Figure 32).…”
Section: Magnetophotonic Crystalsmentioning
confidence: 99%
“…This produces strong alterations in cm-and mm-wave transmission spectra. Golosovsky et al [5] reported that disk shaped magnetic particles can self-assembly into various 3D periodic structures; in continuation Saado et al [6] demonstrated that such magnetic PCs possess PB gaps that can be tuned in the microwave regime by means of an applied magnetic field.…”
Section: Introductionmentioning
confidence: 98%